Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Konsumen (Studi Kasus pada Konsumen Produk Oli Prima XP di Kota Padang) - Edriani, Devi; Harmelia, Harmelia (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
This study aims to analyze and see the effect of Product Quality and Brand Image on consumer purchasing decisions on Prima XP oil products in the city of Padang. This type of research is quantitative research. The population of this study is consumers of Prima XP oil users in the city of Padang. Instrument testing uses validity and reliability tests. Data analysis using descriptive analysis and inductive analysis, namely normality test, heterocedasticity test and multicollinearity test and hypothesis testing using multiple regression analysis, F test and t test, from processing the data obtained results Y = 24,426 + 0,499 X1 + 0,450 X2. The results of these studies indicate that, 1) Product Quality has a significant effect on Consumer Purchasing Decisions, 2) Brand Image has a significant effect on Consumer Purchasing Decisions, 3) Product Quality and Brand Image together have a significant effect on Consumer Purchasing Decisions.